Cu2O Nanocrystal Model Catalysts. Issue 7 (23rd January 2022) - Zhang, Zhenhua; You, Rui; Huang, Weixin
Comprehensive Summary: Model catalysts approach is widely adopted in fundamental studies of complex heterogeneous catalysis. Traditional model catalysts are single crystal‐based model catalysts, whose results, however, sometimes suffer from the "material gap" and "pressure gap" when applied to working catalysts. Recently, uniform catalytic nanocrystals with well‐defined structures have emerged, and we have put forward a concept of nanocrystal‐based model catalysts for fundamental studies of complex heterogeneous catalysis under conditions approaching working catalysts as closely as possible. In this perspective, we summarize our research progresses on Cu2 O‐based nanocrystal model catalysts. Following a brief introduction, we summarize controlled synthesis of uniform Cu2 O nanocrystals with various morphologies, morphology‐dependent surface compositions and structures and surface chemistry of uniform Cu2 O nanocrystals, and heterogeneous catalysis of Cu2 O‐based nanocrystals. Finally, we conclude the concept of nanocrystal‐based model catalysts and outlook that uniform nanocrystals can act not only as model catalysts but also as efficient catalysts. What is the most favorite and original chemistry developed in your research group? By far, the most favorite and original chemistry developed in my research group is the concept of "nanocrystal model catalysts", which overcomes the so‐called "materials gap" and "pressure gap" encountered by the research field of surface chemistry for heterogeneous catalysis using traditional single crystal model catalysts. How do you get into this specific field? Could you please share some experiences with our readers? Surface chemistry studies of single crystal model catalysts had been considered to be able to achieve the fundamental understanding of complex heterogeneous catalysis before the "materials gap" and "pressure gap" were found to exist between single crystal model catalysts and working powder catalysts. Since then, to overcome the "materials gap" and "pressure gap" has been a main goal of the research field of surface chemistry for heterogeneous catalysis. I established my research group in 2004 when catalytic nanocrystals with uniform and well‐defined surface structures emerged quite a lot, and then had the idea of using nanocrystals as a novel type of model catalysts for fundamental studies of complex heterogeneous catalysis under conditions approaching working catalysts as closely as possible. Our work has successfully validated the concept of "nanocrystal model catalysts". Therefore, my experience is to bear the important problems of the research field in mind and keep learning new knowledge from related research fields. What is the most important personality for scientific research? In my personal opinion, intuitivism, persistence, and self‐motivation are the most important personalities for scientific research. What is your favorite journal(s)? I prefer to publish my papers in journals that have large readerships so that the reported new knowledge can be widely shared. What are your hobbies? What's your favorite book(s)? My hobbies are the things that do not need thinking and special attention. These things make me truly relaxed. My favorite books are history of science with comments written by famous scientists (translated) in Chinese. If you have anything else to tell our readers, please feel free to do so. Scientific research is full of inter‐transformed frustration and happiness, but allows one to demonstrate the intelligence and capability freely and independently. Abstract : The article briefly reviews a concept of uniform oxide nanocrystal model catalysts for fundamental studies of complex heterogeneous catalysis, using Cu2 O‐based nanocrystal model catalysts as an example.